2014
DOI: 10.4149/endo_2014_01_35
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport in brain – effect of inflammation

Abstract: Glucose is transported across the cell membrane by specific saturable transport system, which includes two types of glucose transporters: 1) sodium dependent glucose transporters (SGLTs) which transport glucose against its concentration gradient and 2) sodium independent glucose transporters (GLUTs), which transport glucose by facilitative diffusion in its concentration gradient. In the brain, both types of transporters are present with different function, affinity, capacity, and tissue distribution. GLUT1 occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 0 publications
3
78
0
2
Order By: Relevance
“…Supporting these findings, high energy diets have been previously shown to influence GLUT2 [83] as well as IR expression in the brain [84]. A positive effect of GLUT2 on hippocampal synaptic activity, neurotransmitter release, and cognition has been previously reported [85, 86], while others have suggested involvement of insulin receptors in hippocampal dependent spatial learning and memory [8789] as well as recognition memory [9092]. In another series of studies, intracerebroventricular injection of streptozotocin, a drug specific to GLUT2 dependent transport [93], was shown to decrease IR expression only in the CA3 region of the rat’s hippocampus [94], and was found to be associated with memory impairments [95].…”
Section: Discussionmentioning
confidence: 56%
“…Supporting these findings, high energy diets have been previously shown to influence GLUT2 [83] as well as IR expression in the brain [84]. A positive effect of GLUT2 on hippocampal synaptic activity, neurotransmitter release, and cognition has been previously reported [85, 86], while others have suggested involvement of insulin receptors in hippocampal dependent spatial learning and memory [8789] as well as recognition memory [9092]. In another series of studies, intracerebroventricular injection of streptozotocin, a drug specific to GLUT2 dependent transport [93], was shown to decrease IR expression only in the CA3 region of the rat’s hippocampus [94], and was found to be associated with memory impairments [95].…”
Section: Discussionmentioning
confidence: 56%
“…The insulin-independent glucose transporter GLUT3 is the major glucose transporter in neurons and is present in very few other cell types in the body. The density and distribution of GLUT3 in axons, dendrites and neuronal soma correlates with local cerebral energy demands 74 . Insulin is not required for GLUT3-mediated glucose transport; instead, NMDA receptor-mediated depolarization stimulates consumption of glucose, which prompts glucose uptake and utilization via GLUT3 73,75 .…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…Glucose transporters GLUT1 and GLUT3 are responsible for glucose transport into the Schwann cell while GLUT3 is the primary transporter in axons (Magnani et al, 1996). Fructose uses a different transporter GLUT5 at least in microglia (Jurcovicova, 2014). Increased expression of GLUT5 as has been demonstrated with GLUT1 and GLUT3 due to anoxia (Zovein et al, 2004;Li et al, 2013) would increase fructose flux into the cell and contribute to the observed results.…”
Section: Sites Of Anoxic Alterations In Metabolic Pathwaysmentioning
confidence: 86%